The ethics of organizational change in healthcare - Ferrari, Antonio; Manotti, Pietro; Balestrino, Antonio; Fabi, Massimo (Acta Biomedica Atenei Parmensis, 2018)
The article addresses the increasingly important issue of organizational ethics in healthcare. Assuming that the governance of organizational change consists of a seriousness of continuous choices and of objectives to be determined and achieved, a possible definition of this new discipline is then deepened, and its fields of application are identified.In the discussion therefore emerge the close link between ethical choice in organization and legality, passing through transparency and prevention of corruptive phenomena. After a focus on the strategic role played by the Medical Doctor of the healthcare management team, in conclusion, the need arises to support a strengthened supervisory and evaluation system and a culture of the ethical organizational choice of health managers, a rooting of the sense of identity and belonging to the healthcare organization and its mission by Professionals. Also governing this last aspect is the new challenge for the management of public healthcare enterprises.